PEMAKNAAN JANJI POLITIK CALON PRESIDEN PRABOWO SUBIANTO-SANDIAGA UNO DI KOMPAS TV - Glenys Octania (JIKE: Jurnal Ilmu Komunikasi Efek, 2019)
Abstract Presidential candidate Prabowo - Sandi promised to fight for Emak-enak. The political promise to fight for Emak-emak is highlighted in the mass media coverage, both electronic, print and online. Election campaigns using mass media are very optimally utilized. Prospective couples use mass media to convince voters to offer a vision and mission as well as work programs. Like one of them is Kompas Tv coverage. The purpose of this study was to understand the meaning of the members of the Berhijab Journalist community regarding the reporting of political promises after candidate number 02 at Kompas Tv. This study uses qualitative research with interpretive paradigms. The method used is reception analysis. Data is collected through interviews and observations. The informant of this study was a member of the Berhijab Journalist Community. The results of this study indicate that the acceptance of political pledge promises 02 by KJB was accepted differently. The background of work, family to experience in the past was a decoding factor towards the pledge of Politics of candidate pairs 02. The results showed that informants were spread in three public positions which referred to Stu Hall Hall's theory of audience that the analysis of audience receptions was divided into three meaningful positions namely dominant-hegemonic reading , negotiated reading and oppositional reading. Keywords: reception, election, Emak-emak, kompass TV, politic communication